Preservation of Titanium in a Naringin-Containing Solution to Enhance Osteogenic and Anti-inflammatory Activities In Vitro - Chen, Wei; Zhu, Wen-qing; Su, Shan; Liu, Yao; Qiu, Jing (Frontiers in Materials, 2022)
When exposed to air, the titanium implants undergo changes in surface characteristics and biological activity, which is known as biological aging. It is important to find a suitable storage method to slow down the biological aging of titanium. The purpose of this study was to develop a naringin-containing storage solution and evaluate the effects of this storage method on physicochemical properties as well as osteogenic and anti-inflammatory activities of commercial pure titanium (cp-Ti) and sandblasted with large grit and acid-etched titanium (SLA-Ti). Titanium surfaces stored in air and 0.9% NaCl solution for 4 weeks were served as control, and samples submerged in three different concentrations of naringin-containing solution for 4 weeks were used to investigate the new storage method. Surface topography images showed that nanostructures were observed on liquid-stored SLA-Ti surfaces. The storage condition did not influence the roughness of both cp-Ti and SLA-Ti. However, the wettability of titanium varied with the storage methods. Titanium stored in the naringin-containing solution exhibited lower contact angles. Samples stored in aqueous solution were less susceptible to hydrocarbon contamination. The preservation of titanium in the 10 μM naringin-containing solution enhanced the adhesion, proliferaton, and differentiation of osteoblasts. In addition, macrophages on samples stored in 10 μM and 100 μM naringin-containing solutions displayed better anti-inflammatory effect. In summary, the 10 μM naringin-containing solution could enhance osteogenic and anti-inflammatory activities of titanium and was proved to be an effective new storage condition.